OP0085 THE CHANGING STATES OF FIBROMYALGIA IN A LONGITUDINAL COHORT OF PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Aarrestad Provan, S.; Dean, L.; Jones, G. T.; Macfarlane, G.
Abstract : Background: The identification of predictors for longitudinal fibromyalgia (FM) development has been identified as a research priority in a recent systematic review and meta-analyses (1). This paper examines the longitudinal development of, or recovery from, FM in patients with axial Spondyloarthritis(axSpA). Objectives: To identify predictors for FM development and recovery in patients with axSpA. Methods: The British Society of Rheumatology Biologics Register (BSRBR-AS) recruited patients with axSpA from 83 centres in a prospective study. Fibromyalgia was diagnosed using the self-reported Fibromyalgia Survey Diagnostic Criteria (FSDC). Measures of axSpA disease activity and clinical findings were recorded at regular intervals. We identified predictors for developing FM, and for recovering from FM, between yearly visits using uni- and multivariate logistical regression models. Results: Eight hundred and one patients had two or more visits and were eligible for inclusion. 686 patients did not have FM at baseline, of whom 45 had developed FM by follow-up. 115 patients had FM at baseline, of whom 77 had recovered by follow-up. The uni- and multivariate models are presented in table 1 . Conclusion: The development of FM in patients with axSpA can be predicted by high levels of axSpA activity and presence of widespread pain, while low levels of the same variables, and starting a TNF-inhibitor predict recovery from FM. The presence of co-morbid FM should be considered in patients with a history of high axSpA disease activity and wide spread pain. References: [1]Zhao SS, Duffield SJ, Goodson NJ. The prevalence and impact of comorbid fibromyalgia in inflammatory arthritis. Best Pract Res Clin Rheumatol. 2019;33(3):101423. Disclosure of Interests: Sella Aarrestad Provan Consultant of: Novartis, Linda Dean: None declared, Gareth T. Jones Grant/research support from: Pfizer, AbbVie, UCB, Celgene and GSK., Gary Macfarlane: None declared